2002
DOI: 10.1093/geront/42.4.552
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Commercial-Grade Carpet on Postural Sway and Balance Strategy Among Older Adults

Abstract: Healthy, older adults did not have difficulty maintaining static balance on the carpeted surface; however, the results could be different if participants who had a history of falling had been included. The results from this study are important and provide a basis of comparison for those individuals who have experienced more than two falls in the last 6 months or who have a history of falling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…With regards to concurrent validity, examination of the Bland-Altman plots reveals a small difference in COP path length values between the two devices. These disparate values were consistent between days, and were possibly due to device specific factors such as the precision and sensitivity of the sensors or the difference in surface texture and hardness [7]. The consistency of the within-device results indicates that this would not have an effect on comparisons performed on patients using the same device.…”
Section: Discussionmentioning
confidence: 74%
“…With regards to concurrent validity, examination of the Bland-Altman plots reveals a small difference in COP path length values between the two devices. These disparate values were consistent between days, and were possibly due to device specific factors such as the precision and sensitivity of the sensors or the difference in surface texture and hardness [7]. The consistency of the within-device results indicates that this would not have an effect on comparisons performed on patients using the same device.…”
Section: Discussionmentioning
confidence: 74%
“…Compared to rigid surfaces, compliant foam surfaces have been associated with increased postural sway during quiet stance [46][47][48][49], as well as a lowered trajectory of the whole-body centre-of-mass (COM), reduced toe clearance, and increased step length, step width, and step width variability during gait [50,51]. Regarding common compliant flooring systems tested in this study, thick carpet has been shown to increase anterior-posterior sway for older adults when visual fields are altered [46], although these effects are not observed under normal vision conditions [52,53]. Regarding novel compliant flooring systems, Laing and Robinovitch [18] found that medial-lateral postural sway on a SmartCell floor was not different than on a rigid surface for community-dwelling elderly women, and that scores on the Timed Up and Go test (a predictor of fall risk [54][55][56]) were not different for SmartCell, SofTile and a rigid floor condition.…”
Section: Discussionmentioning
confidence: 81%
“…Redfern et al [33] and Dickinson et al [34,35] varied flooring surfaces between relatively rigid and carpeted flooring conditions and reported significant effects on center of pressure measures only for older participants (mean age >72 years in all studies) when subjected to moving visual environments or eyes closed, translating floor conditions. One potential interpretation of these results is that the added compliance associated with carpeted conditions impairs proprioceptive feedback at the ankle joints, but that these impairments are insufficient to significantly influence postural control until proprioceptive input gains are increased during periods of visual feedback interference.…”
Section: Discussionmentioning
confidence: 97%